Study on the coupling coordination characteristics and influencing factors of ecological environmental civilization and resident public health in China-based on a modified coupling coordination model. - Qian Xie; Yongkai Wang; Yingchun Zhang (PLoS ONE)
As industrial technologies advance, climate change and environmental pollution increasingly pose threats to human health. This study examines the coupling coordination characteristics between ecological environmental civilization (EEC) and resident public health (RPH) to promote both higher public health standards and enhanced societal sustainability. Utilizing panel data from 31 provinces in China spanning from 2010 to 2022, this paper constructs evaluation indices for EEC and RPH. Initially, the entropy method is employed to determine the development levels of each domain. Subsequently, a modified coupling coordination degree (CCD) model is applied to assess the CCD between EEC and RPH. This research further investigates the spatiotemporal evolution trends of the CCD using methods such as the Dagum Gini coefficient, kernel density estimation (KDE), and Markov chains. Finally, the panel Tobit model is utilized to analyze factors influencing the CCD. Findings reveal that during the study period, both EEC and RPH in China exhibited a stable upward trend, although the overall development level remained relatively low. The CCD showed consistent growth both nationally and across three major regions. Overall inequality in coupling coordination, as measured by Dagum Gini coefficient, has decreased, with the coefficient reducing from 0.0316 in 2010 to 0.0199 in 2022. KDE results indicate a rightward shift in the density curve of the CCD, suggesting a significant reduction in absolute disparities. Panel Tobit regression analysis shows that economic development, urbanization, and education levels significantly and positively influence the CCD on a national scale, with urbanization having the most substantial impact, followed by economic development and education levels.